The effects of water-CuO nanofluid flow on heat transfer inside a heated 2D channel - Najafabadi, Mohsen Khalili; Bognár, Gabriella; Hriczó, Krisztián (Design of Machines and Structures, 2022)
The velocity distribution and heat transfer improvement in a two-dimensional channel filled with a water-CuO nanofluid is numerically studied. The nanofluid flow is assumed laminar and one-phase with Newtonian behaviour. Pure water is considered as the base fluid, and water-CuO nanofluid with four different volume fractions of CuO nanoparticles are examined. A constant heat source–sink is considered to cover the entire length of the bottom wall of the channel while the upper wall is assumed thermally insulated. The control volume technique is used to discretize the governing differential equations, and the SIMPLE algorithm is used to solve the velocity-pressure coupling. A CFD simulation is applied on nanofluid flow utilizing ANSYS FLUENT to solve the governing equations of the flow. The effects of nanoparticle volume fraction on the heat transfer, velocity profile, wall shear stress, skin friction coefficient, and Nusselt number along the channel have also been examined. The results confirm that the volume fraction of nanoparticles plays an important role in heat transfer enhancement and hydrodynamic behaviour of flow. The results are presented in figures and tables.